2012
DOI: 10.1186/1744-9081-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Representational change and strategy use in children's number line estimation during the first years of primary school

Abstract: BackgroundThe objective of this study was to scrutinize number line estimation behaviors displayed by children in mathematics classrooms during the first three years of schooling. We extend existing research by not only mapping potential logarithmic-linear shifts but also provide a new perspective by studying in detail the estimation strategies of individual target digits within a number range familiar to children.MethodsTypically developing children (n = 67) from Years 1-3 completed a number-to-position numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 49 publications
11
67
0
1
Order By: Relevance
“…However, overall accuracy performance in comparison is not a direct manifestation of the underlying logarithmic compression of the mental number line; the DE and the SE are. Moreover, although the performance in number comparison and number line estimation are thought to reflect characteristics of the same underlying mental number line, recent work also pointed towards a different origin of these effects (e.g., connectionist models about comparison; Verguts, Fias, & Stevens, 2005; and non-numerical processes such as proportion judgments - Barth & Paladino, 2011, attention resources -Anobile, Cicchini, & Burr, 2012or strategy use -Petitto, 1990White & Szücs, 2012 in case of number line estimation performance). Finally, Laski and Siegler (2007) presented symbolic numbers between 0-100.…”
Section: Introductionmentioning
confidence: 99%
“…However, overall accuracy performance in comparison is not a direct manifestation of the underlying logarithmic compression of the mental number line; the DE and the SE are. Moreover, although the performance in number comparison and number line estimation are thought to reflect characteristics of the same underlying mental number line, recent work also pointed towards a different origin of these effects (e.g., connectionist models about comparison; Verguts, Fias, & Stevens, 2005; and non-numerical processes such as proportion judgments - Barth & Paladino, 2011, attention resources -Anobile, Cicchini, & Burr, 2012or strategy use -Petitto, 1990White & Szücs, 2012 in case of number line estimation performance). Finally, Laski and Siegler (2007) presented symbolic numbers between 0-100.…”
Section: Introductionmentioning
confidence: 99%
“…These tasks have been used in previous research (Halberda, Mazzocco, & Feigenson, 2008;Van der Ven, Kroesbergen, Boom & Leseman, 2012;White & Szucs, 2012). All tasks were administered on a laptop and all were programmed in E-Prime with the exception of the comparison task which was delivered using Panamath software .…”
Section: Research Design and Proceduresmentioning
confidence: 99%
“…was completed on a 0-100 number line and adapted from the work of White and Szucs (2012). Children were presented with a number line, after a short delay (1000ms) the target digit appeared in the left corner of the screen.…”
Section: Number Processing Tasksmentioning
confidence: 99%
“…The use of alternative model-fitting approaches has generated interesting research findings and has contributed to a discussion about the number line task and that different aspects may affect children's number line estimations and that children's estimation patterns on number line tasks may not be a reflection of their internal representation of number (e.g., Barth & Paladino, 2011;Bouwmeester & Verkoeijen, 2012). For example, task specific properties such as marked and fixed endpoints (reference points) (Barth & Paladino, 2012;Rouder & Geary, 2014;White & Szűcs, 2012) as well as children's number knowledge (Ebersbach et al, 2008;LeFevre, Sowinski, Cankaya, Kamawar, & Skwarchuk, 2013) and estimation strategies (Ashcraft & Moore, 2012;Rouder & Geary, 2014) may affect their ability to estimate number on number line tasks. The possible influence of individual children's strategies when estimating numbers on number line tasks was mentioned by Siegler and Booth (2004), but Barth and Paladino (2011) and Peeters, Degrande, Ebersbach, Verschaffel and Luwel (2015) discussed children's use of different estimation strategies and argue for the need of alternative model fitting approaches when analyzing children's number line estimates in order to capture the variation and characteristics in children's estimations of number.…”
Section: Agementioning
confidence: 99%
“…In line with their hypothesis, Barth and Paladino (2011) found that "proportion-judgment models provide a unified account of estimation patterns that have previously been explained in terms of a developmental shift from logarithmic to linear representations of number" (Barth & Paladino, 2011, p. 125). Furthermore, White & Szűcs (2012) found that children employ various strategies when estimating numbers on number lines. The 6-year-old children included in their study mainly used the lower reference point (i.e., 0) when making estimations of number on a 0-20 number line task while somewhat older children used more advanced estimation strategies and where able to use more referents making their mumber line estimations.…”
Section: Agementioning
confidence: 99%